The psychology of sport and performance injury an interprofessional case-based approach - Arvinen-Barrow, Monna; Clement, Damien (Routledge, 2019)
The use of psychological interventions and counselling strategies has become a central part of injury prevention, rehabilitation, and return to participation process. The Psychology of Sport and Performance Injury: An Interprofessional Case-Based Approach is the first book to offer students, academic scholars, and practitioners case studies that are grounded in psychological theory and empirical evidence, with a specific focus on addressing psychological aspect of sport and performance injuries in an interprofessional manner. This book presents nine "real-life inspire" fictional sport and performance injury cases. It demonstrates the viability and effectiveness of adopting an interprofessional, person-centered approach to injury, rehabilitation, and return to participation process. Each case is focused on a particular phase of rehabilitation, with specific attention placed on relevant biopsychosocial concerns. Within each chapter, a theoretical, conceptual, and empirical analysis of the case is presented followed by detailed accounts on how a range of professionals and significant others can work alongside each other to provide a holistic care for the injured performer within their own competencies